(untitled) (Herald of Journalism, 2021)
Since the beginning of 2020, the issue of personal protection against the dangerous disease COVID-19 has been relevant. One of the simpler precautions recommended by WHO for the general public is wearing a mask. The surge in demand for protective masks has led to severe shortages and higher prices for them. The purpose of this study is to analyze the Kazakhstani market of protective masks using the example of ECOS, which since 2013 has been producing filtering half masks that comply with the register of imported and demanded goods with protection class FFP1, FFP2 and FFP3. Also study their design and the presence of the company in the media, since the success of any company depends on how well the brand is recognized in society. The main direction of scientific research is design, PR, marketing. Any product is based on a design concept, which is as important and necessary as PR when launching new products. PR as an effective tool for marketing communications is getting stronger as information noise grows, competition intensifies and media fragmentation increases. The media act as an intermediary between the company and the end consumer, and indirectly influence the end consumer. The research methodology is based on the methods of collecting primary information and their processing. The value of this work is that students will learn to analyze the design according to key quality criteria and evaluate the product according to its main aspects. Further research in this direction can greatly help designers, PR specialists and others when developing a concept and strategy for the development of new products. Key words: design, PR, media, mask, respirator, design quality criteria.